EVALUASI INVESTASI UNIT REHABILITASI MEDIK EFEKTIF DAN EFISIEN DI RUMAH SAKIT UMUM BIDADARI BINJAI - Aditya Dewi, Esti; Purwadhi, Purwadhi; Veranita, Mira (LP2M Universitas Bina Bangsa, 2025)
Bidadari Binjai Hospital carries out investment in the form of the development of the Medical Rehabilitation Service Unit which has been running for 1 year, an assessment is carried out using ratios based on information from Cash Flow analysis, Payback Period analysis, Net Present Value analysis and Internal Rate of Return analysis. By conducting a financial analysis, hospitals know the investment risks, so hospitals need to implement a risk management process with solid managerial functions in Planning, Organizing, Actuating and Controlling to be able to achieve effective and efficient services so that the risk of loss can be anticipated. The type of research used in this study is qualitative research with a case study approach and data used quantitatively in the form of documentation and financial data of the hospital. The results of the calculation using the PP (Payback Period) Method show that the return on investment costs is achieved within a period of 1 year and 3 months. Analysis with the NPV (Net Present Value) method obtained a positive value of Rp. 3,556,095,947 analysis of the IRR (Internal Rate of Return) method obtained an interest rate of 9.8%. so that this investment can be said to be